Implementing BOOM in Designing a Knowledge Management System for the Information Systems Study Program at Dian Nuswantoro University - Sani, Ramadhan Rakhmat; Sukamto, Titien S.; Rohmani, Asih; Maszuda, Akbar Alvian (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2025)
Knowledge management within the Information Systems Study Program at Dian Nuswantoro University is currently still at an ineffective stage. Although the program focuses on the development and distribution of information systems, the lack of an implemented Knowledge Management System (KMS) has hindered the effective organization and utilization of knowledge within the department. By implementing a KMS, the program could more easily manage, store, and collaborate on knowledge assets. To address this issue, a web-based KMS design is proposed using the Business Object Oriented Modelling (BOOM) method. This method involves several stages: SWOT (Strengths, Weaknesses, Opportunities, and Threats) analysis, discovery, construction, and final verification and validation—each aimed at optimizing knowledge management within the academic scope of the study program. The design process was supported by data collected through questionnaires distributed to both faculty members and students. The final output of this study includes a test scenario and user interface design for the Information Systems Program's Knowledge Management System website. This proposed design is expected to enhance and streamline knowledge management within the department.